Dari Ruang Taklim ke Institusi Dakwah: Transformasi Majelis Taklim Darusshofa di Kota Medan (2000–2026) - Muhammad Fajar Aditya Zain; Achiriah Achiriah (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
Rapid urban transformation has increased the need for non-formal Islamic educational institutions that strengthen both religious values and social cohesion. This study examines the history and development of the Darusshofa Majelis Taklim in Medan, the implementation of its da'wah activities, and its significance as a religious institution amid modernization. Employing a qualitative descriptive-analytical design, the research applies a historical approach to reconstruct the institution's development through in-depth interviews, observations, and documentation, with data analyzed through data reduction, data display, and conclusion drawing. The novelty of this study lies in integrating historical reconstruction with an analysis of the institutional development and socio-religious contribution of the Darusshofa Majelis Taklim within an urban context. The findings show that the institution originated from a local da'wah initiative pioneered by KH. Mufty Ahmad Nasichin, who successfully integrated Islamic teachings with community realities. Its activities promote spiritual education, strengthen social solidarity, and reinforce religious identity. Despite challenges arising from social change, urban lifestyles, and limited youth participation, the Darusshofa Majelis Taklim has remained a sustainable model of community-based da'wah and non-formal Islamic education in Medan.